Suborbital Space Tourism : Doozy Experiences Beyond Earth - Jaskari, Minna-Maarit; Jauffret, Marie-Nathalie; Kauppinen-Räisänen, Hannele (Palgrave Macmillan, 2024)
This chapter delves into the experiences of actual space travelers, focusing on their experiences along the journey. The underlying premise is that the experiences occurring in various phases of the journey—pre, during, and after—each play a crucial role in shaping the holistic travel experience. In order to gain in-depth insights regarding these experiences, a qualitative study was designed using mixed methods comprising three one-to-one interviews, analysis of published interviews with six space travel astronauts, and archival data. The study contributes with insights into the unique circumstances of space travel and lived experiences of such journeys. It also introduces the concept of “doozy tourism” to illustrate the specific nature of space tourism, which is here characterized as a niche of luxury tourism. Finally, it shows how experiences within space tourism are divided into four phases. The study also holds managerial implications for luxury space tourism.
Keywords: Suborbital space tourism; Tourism experience; Doozy tourism; Luxury tourism; Space travel experience; Prolonged waiting time; Qualitative research; fi=Markkinointi|en=Marketing|